Effective Exchange Rates and Merchandise Flows - an Empirical Analysis of Polish Foreign Trade - Michalczyk, Wawrzyniec (Kursy efektywne a przepływy towarowe - analiza empiryczna polskiego handlu zagranicznego, 2010)
The author attempts to analyse links between merchandise flows in Polish foreign trade and the evolution of nominal and real exchange rate of zloty. As it turns out, the relations between the variables look similar like in theory although not in an entirely clear way. Essentially, however, the strengthening of zloty inhibits exports and stimulates imports, while reducing the income from the sale of goods abroad and increasing spending on imports results in the depreciation of Polish currency. Conducted econometric analysis indicates such connections; however, it is fraught with a large margin of error. On the other hand, the analysis of correlation coefficients suggests a positive relation between exchange rate and the size of trade, which, however, results to a large degree from a close link between the volume of imports and exports.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 92-105
Keywords: exchange rate; foreign trade; merchandise flows